Genetic resistance to yellow rust infection of the wheat ear is controlled by genes controlling foliar resistance and flowering time. Issue 5 (29th July 2022) - Bouvet, Laura; Percival‐Alwyn, Lawrence; Berry, Simon; Fenwick, Paul; Holdgate, Sarah; Mackay, Ian James; Cockram, James
Abstract: Yellow rust (YR), or stripe rust, is a fungal infection of wheat ( Triticum aestivum L.) caused by the pathogen Puccinia striiformis Westend f. sp. tritici ( Pst ). Although much research has focused on YR leaf infection, we are not aware of studies investigating the genetic control of YR resistance in the wheat ear. Using an eight‐founder multiparent advanced generation intercross (MAGIC) population, we identified five quantitative trait loci (QTL) controlling glume YR resistance in wheat ears. Of these, three ( QYrg.niab‐2D.2, QYrg.niab‐4D.1, and QYrg.niab‐5A.1 ) collocated with leaf YR resistance QTL previously identified in the same population. We find evidence that QYrg.niab‐5A.1 likely corresponds to the adult plant resistance locus Yr34 introgressed from einkorn wheat ( T. monococcum L. subsp. monococcum ), and that resistance at QYrg.niab‐2D.2 also likely originated from a chromosomal introgression from a wheat relative. The two remaining glume YR resistance QTL were linked to genetic loci controlling flowering time, with early flowering alleles conferring reduced glume YR resistance. The association between earlier flowering and increased glume infection is likely due to the emergence of the ear during environmental conditions more favorable for Pst infection. Collectively, these first insights into the genetic control of YR resistance in glumes provides specific genetic targets for the control of YR resistance in both the leaves and the glumes and will be especially relevant to wheat grown in Pst ‐prone agricultural environments where earlier flowering is favored. Core Ideas: Puccinia striiformis Westend f. sp. tritici ( Pst ) causes yellow rust (YR) in wheat leaves and ears. We present the first reports for the genetic control of YR on the wheat ear. Ear YR infection is controlled by subsets of QTL controlling leaf resistance and flowering time. The findings are relevant to wheat breeding for Pst ‐prone environments.